The Influence Of Leadership And Organizational Culture On Operational Efficiency Through Work Discipline at PT. Ekadharma International Tbk - Efrianza; Sutoyo; Koen Irianto Uripan; Sutomo; Immanuel Ustradi Osijo (PT Maju Malaqbi Makkarana, 2026)
This study aims to analyze the influence of leadership and organizational culture on operational efficiency through work discipline at PT Ekadharma International Tbk. Operational efficiency is an important factor in improving the company's competitiveness, which is influenced by leadership quality, organizational cultural values, and employee work discipline levels. This study uses a quantitative approach with a survey method. Data was collected through the distribution of questionnaires to employees of PT Ekadharma International Tbk, who were used as research respondents. The data analysis techniques used are descriptive statistical analysis and path analysis to test the direct and indirect influence between variables. The results of the study show that leadership and organizational culture have a positive and significant effect on work discipline. Furthermore, work discipline has a positive and significant effect on operational efficiency. In addition, leadership and organizational culture also indirectly affect operational efficiency through work discipline as an intervening variable. Based on the results of the study, it can be concluded that increasing the company's operational efficiency can be achieved through the implementation of effective leadership, strengthening a positive organizational culture, and improving employee work discipline. This research is expected to contribute to company management in formulating more effective human resource policies.